Polymorphic loci of coat color in mini-pigs - S. V. Nikitin; K. S. Shatokhin; S. P. Knyazev; G. M. Goncharenko; V. I. Zaporozhets; V. I. Ermolayev (Вавиловский журнал генетики и селекции)
The present work is phenomenological and purely descriptive. It shows polymorphism of colors in a breeding group of mini-pig in the Institute of Cytology and Genetics of the Siberian Branch of the Russian Academy of Sciences (ICG SB RAS) and makes some assumptions about the nature of this genetic diversity. In the ICG SB RAS mini-pig herd, wild-type coloration (agouti), black-spots, black and white color are present. All these options have variants, including previously undescribed, with genetically determined differences. In addition, the ICG SB RAS mini-pigs have variants inherent only to heterozygous individuals and archaic gray color described only in primitive domestic pig. Comparison of the observed color phenotypes in the breeding with literature data showed that EDNRB, KIT, KITLG and the MC1R are polymorphic loci, while ASIP, OCA2 and TYRP1 are monomorphic loci. Thus, the loci that control the most common coat colors in domestic pigs are polymorphic, while those controlling rare or relatively rare colors and monomorphic. The research allowed us to put forward some assumptions concerning the genetic determination of the phenotypic characteristics of color seen in the study group selection. Among these assumptions is one about the genetic control of juvenile colors in domestic pigs. Observations made in the ICG SB RAS mini-pig breeding group allowed us to examine and describe the features of age-related changes of an embodiment of black-motley suit, when newborn piglets originally have black-and-motley fur color on the brick-red background and at an age of one year, a gray roan background formed by a mixture of white and black hairs. In addition, it was shown that with the help of technical means black spots can also be detected on a black background.